2011
DOI: 10.1016/j.ijrobp.2010.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ultrahigh Baseline PSA Levels on Biochemical and Clinical Outcomes in Two Radiation Therapy Oncology Group Prostate Clinical Trials

Abstract: Purpose To assess ultra-high (UH; PSA ≥ 50 ng/ml) patient outcomes compared to other high-risk patients and to identify outcome predictors. Methods and Materials PCP from two Phase III RTOG clinical trials (9202 and 9413) were divided into two groups; high-risk patients with and without UH baseline PSA level. Predictive variables included age, Gleason score, clinical T stage, KPS, and treatment arm. Outcomes included overall survival (OS), distant metastasis (DM), and biochemical failure (BF). Unadjusted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Our results are consistent with the work of others [17][18][19][20][21] showing that, although a very high PSA level portends a poorer prognosis compared with other N0M0 prostate cancer, these presentations may still frequently be curable. Clinical trials establishing the curative role of locoregional treatment and adjuvant hormonal therapy have included men with PSA levels of 50 to 160 ng/mL, 5,22,23 although these studies were not designed to determine whether the subpopulation of men with a very high PSA level could benefit from locoregional treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with the work of others [17][18][19][20][21] showing that, although a very high PSA level portends a poorer prognosis compared with other N0M0 prostate cancer, these presentations may still frequently be curable. Clinical trials establishing the curative role of locoregional treatment and adjuvant hormonal therapy have included men with PSA levels of 50 to 160 ng/mL, 5,22,23 although these studies were not designed to determine whether the subpopulation of men with a very high PSA level could benefit from locoregional treatment.…”
Section: Discussionsupporting
confidence: 93%
“…A pooled analysis of 2 RTOG trials suggested that patients with a PSA level $50 ng/mL have a higher adjusted rate of biochemical failure, distant metastasis, and mortality compared with other high-risk patients, but the effect size was modest, with similar unadjusted rates of 7-year OS compared with those with a PSA level ,50 ng/mL (64.3% vs 68.0%); there was no comparison with a cohort of node-positive patients. 17 A Canadian registry study showed that among 207 patients with a PSA level $100 ng/mL, radiation therapy was associated with improved 5-year OS compared with ADT alone (68% vs 40%). 18 Several institutional studies have similarly shown good long-term outcomes for patients with very high PSA levels, albeit inferior to outcomes for patients with lower PSA levels.…”
Section: Discussionmentioning
confidence: 99%
“… 1,5 In localized PCa, serum PSA has been demonstrated to correlate with the pathological stage, Gleason score, and the probability of organ-confined disease 7,8 ; whereas, in metastatic PCa, PSA has been shown to reflect the disease burden, and its post-hormone therapy response serves as a predictor of overall survival. 9 However, in a number of previous population-based observational studies, a PSA level >50 ng/mL was observed to correlate with extreme-risk patients, who showed a worse response to treatment and survival outcome than other high risk patients. 7,9,10 Therefore, it is conceivable that the high risk population includes a subset of patients who are at an extreme risk for disease progression and mortality.…”
Section: Discussionmentioning
confidence: 94%
“…Although ultra-high PSA had a negative impact on overall survival, distant metastases, and biochemical failure, the authors did not view it as a contraindication to local radical therapy. 28 Likewise, Alexander 29 reported good outcomes for patients at a single institution with PSA > 40 ng/mL treated with radiation combined with androgen ablation. Tai et al 10 studied 539 patients listed in the Saskatchewan cancer registry who had a PSAZ50 ng/mL at time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%